Classification of the Mediterranean lowland to submontane pine forest vegetation. Issue 1 (26th January 2021) - Bonari, Gianmaria; Fernández‐González, Federico; Çoban, Süleyman; Monteiro‐Henriques, Tiago; Bergmeier, Erwin; Didukh, Yakiv P.; Xystrakis, Fotios; Angiolini, Claudia; Chytrý, Kryštof; Acosta, Alicia T.R.; Agrillo, Emiliano; Costa, José C.; et al.
Abstract: Aim: Vegetation types of Mediterranean thermophilous pine forests dominated by Pinus brutia, Pinus halepensis, Pinus pinaster and Pinus pinea were studied in various areas. However, a comprehensive formal vegetation classification of these forests based on a detailed data analysis has never been developed. Our aim is to provide the first broad‐scale classification of these pine forests based on a large data set of vegetation plots. Location: Southern Europe, North Africa, Levant, Anatolia, Crimea and the Caucasus. Methods: We prepared a data set of European and Mediterranean pine forest vegetation plots. We selected 7, 277 plots dominated by the cold‐sensitive Mediterranean pine species Pinus brutia, Pinus halepensis, Pinus pinaster and Pinus pinea . We classified these plots using TWINSPAN, interpreted the ecologically and biogeographically homogeneous TWINSPAN clusters as alliances, and developed an expert system for automatic vegetation classification at the class, order and alliance levels. Results: We described Pinetea halepensis as a new class for the Mediterranean lowland to submontane pine forests, included in the existing Pinetalia halepensis order, and distinguished 12 alliances of native thermophilous pine forests, including four newly described and three informal groups merging supposedly native stands and old‐established plantations. The main gradients in species composition reflect elevational vegetation belts and the west–east, and partly north–south, biogeographical differences. Both temperature and precipitation seasonality co‐vary with these gradients. Conclusions: We provide the first formal classification at the order and alliance levels for all the Mediterranean thermophilous pine forests based on vegetation‐plot data. This classification includes traditional syntaxa, which have been critically revised, and a new class and four new alliances. We also outline a methodological workflow that might be useful for other vegetation classification syntheses. The expert system, which is jointly based on pine dominance and species composition, is a tool for applying this classification in research and nature conservation survey, monitoring and management. Abstract : We developed the first formal classification for all the Mediterranean thermophilous pine forests based on vegetation‐plot data. This classification includes both traditional and new syntaxa. We also outline a methodological workflow that might be useful for other large‐scale vegetation classifications. We provide an expert system for applying this classification in research and nature conservation surveys, monitoring and management.